A PROSPECTIVE STUDY OF MULTINATIONAL COMPANY WORKERS’ INTRAOCULAR PRESSURE - Ali, Syed Imran; Tasleem, Sumera; Qudsiya, Sanam Maria (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objective of this study were to find out differences in intraocular pressure (IOP) before and after computer usage and to find out differences in IOP in males and females. Computers have become such a vital part of our daily lives that it is often difficult for us to eliminate our use. The present age is regarded as the computer age. Most of our time goes looking at screens of different forms in laptops, desktop computers, tablets, and mobile phones. Computers use has become a necessity of the present-day world in various professions and it may sometimes require prolonged sessions which can produce strain on the eyes, liable to affect IOP. Methods: The present study includes 100 subjects between 20 and 40 years of age who works continuously for at least 4 h a day on computer screens and individuals without ophthalmological disorders. Schiotz tonometer was used to measure IOP by an ophthalmologist. Results: Our study sample contains 80% males and 20% females, with a manage of 29.29 and 27.55 years, respectively. The increase in IOP value of the left eye after exposure is comparatively more significant in the 6–10 years exposure group (p=0.0000). This finding is similar to the one obtained for the right eye. There is a significant increase in mean IOP values after computer exposure in both males and females. However, the increase is comparatively more significant in males compared to females. Conclusion: There will be a significant increase in IOP after Computer exposure in both genders with a comparatively greater rise of IOP in males than those in females.